Case Report: Acute Myocarditis Due to PD-L1 Inhibitor Durvalumab Monotherapy in a Patient With Lung Squamous Cell Carcinoma - Zhou, Bo; Li, Manxiang; Chen, Tianjun; She, Jianqing (Frontiers in Medicine, 2022)
Background Durvalumab, as a PD-L1 inhibitor, is commonly used for the treatment of various cancers. Adverse events associated with the therapy include hepatitis, nephritis, dermatitis, and myocarditis. Especially, myocarditis as an adverse event after PD-L1 inhibitor therapy is characterized for its low incidence and high mortality. Case Summary Here we present a rare case of a 67-year-old male with lung squamous cell carcinoma complicated with empyema who experienced myocarditis after only PD-L1 inhibitor durvalumab monotherapy. He presented with markedly decrease left ventricular ejection fraction, elevated Natriuretic peptide BNP, Troponin T, Troponin I, ESR, CRP and interleukin-6. The electrocardiogram showed sinus tachycardia, low voltage of limb leads, T wave inversion in anterior waves and V1-V3 QS type. Myocardial injury occurred in a short period and quickly returned to normal after glucocorticoids therapy. Conclusion This case report is of clinical value for the treatment of PD-L1 related myocarditis.